2012
DOI: 10.1007/s10646-012-1022-0
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis on life-history traits: is there such thing as a free lunch?

Abstract: The term "hormesis" is used to describe dose-response relationships where the response is reversed between low and high doses of a stressor (generally, stimulation at low doses and inhibition at high ones). A mechanistic explanation is needed to interpret the relevance of such responses, but there does not appear to be a single universal mechanism underlying hormesis. When the endpoint is a life-history trait such as growth or reproduction, a stimulation of the response comes with costs in terms of resources. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 31 publications
2
60
1
1
Order By: Relevance
“…This question is important because it can determine how hormetic effects may relate to effects at the population level. Jager et al (2013) highlight the important point that organisms have to obey the conservation laws for mass and energy, with the suggestion there may well be "no such thing as a free lunch". These authors present three explanations for observed hormesis, namely increased acquisition (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This question is important because it can determine how hormetic effects may relate to effects at the population level. Jager et al (2013) highlight the important point that organisms have to obey the conservation laws for mass and energy, with the suggestion there may well be "no such thing as a free lunch". These authors present three explanations for observed hormesis, namely increased acquisition (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As emphasised by Jager et al (2013) organisms have to obey the conservation laws for mass and energy and hence trade-off between traits can be expected to be the norm, with implications for the relationship between hormesis effects and fitness.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, generalizations, according to which ''hormetic-like biphasic dose responses may represent a general biological dose-response pattern or strategy'' 11 are not sufficiently supported by scientific evidence. 15,16 Moreover, hormesis merely further defines one response; but most toxicoses have many responses. 10 Some noxious agents can have a cumulative effect or act synergistically with other harmful factors, for example, on the cells with a limited or no potential for cellular regeneration such as cardiomyocytes or neurons.…”
mentioning
confidence: 99%